2018
DOI: 10.3390/molecules23123384
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid Compositions of Resins from Callitris Species (Cupressaceae)

Abstract: The environmental fate of conifer resins and their natural product compounds as mixtures is of importance for source, alteration, and transport studies. The compound compositions of resins of the common Callitris species (Cupressaceae) based on gas chromatography-mass spectrometry have not been reported. Results show that diterpenoids were the most abundant components and callitrisic acid was present in the resin extracts of all Callitris species analyzed. Significant amounts of 4-epi-pimaric and sandaracopima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In addition, sandaracopimaric acid (1) was identified in both species, but at lower concentrations as compared to Widdringtonia. The study by Simoneit et al [21] reported 2 and 3 extensively in most other species of Callitris, which is similar to the pattern evident in Widdringtonia, but these diterpenes were not identified in the two species of Callitris in the current study. Nevertheless, mass spectral analysis can be used to verify if they occur in trace amounts.…”
Section: Chemistry Of Callitrissupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, sandaracopimaric acid (1) was identified in both species, but at lower concentrations as compared to Widdringtonia. The study by Simoneit et al [21] reported 2 and 3 extensively in most other species of Callitris, which is similar to the pattern evident in Widdringtonia, but these diterpenes were not identified in the two species of Callitris in the current study. Nevertheless, mass spectral analysis can be used to verify if they occur in trace amounts.…”
Section: Chemistry Of Callitrissupporting
confidence: 77%
“…Unlike Widdringtonia, interspecific differences in the Genus were pronounced. Major diterpenes in the leaves of C. columellaris were pisiferal (9) and pisiferic acid (10), whereas a single diterpene was evident in C. endlicheri leaves, being isoozic acid (11), which is the isomer of the more widespread ozic acid in other species of Callitris [21]. In addition, sandaracopimaric acid (1) was identified in both species, but at lower concentrations as compared to Widdringtonia.…”
Section: Chemistry Of Callitrismentioning
confidence: 94%
See 2 more Smart Citations
“…In species of pine, fir and spruce, DRAs are core components of chemical and physical tree defense (Phillips and Croteau, ), and have been shown to provide an effective barrier against stem‐boring weevils and associated pathogenic fungi (Robert et al ., ; Lah et al ., ). By contrast, structurally related labdane‐type diterpenoids, such as ferruginol and derivatives thereof, function as defense metabolites in many species of the Cupressaceae (Karchesy et al ., ; Simoneit et al ., ).…”
Section: Discussionmentioning
confidence: 97%